Azerbaijani model of multiculturalism (Journal of Philosophy Culture and Political Science, 2018)
In the modern world there are set of models and types of multicultural societies. Various approaches to the term of multiculturalism confirm that this phenomenon has very complex and special structure. Having analyzed a set from them, it is possible to allocate four main models of multiculturalism and by that to show uniqueness and applicability of the Azerbaijani model of multiculturalism. In article the characteristic is given to a concept of multiculturalism, the known models of multiculturalism in the world are considered.Problems of multiculturalism are considered and discussed in modern works on cultural science, political science, philosophy and sociology. The policy of multiculturalism is the reply of the national state to a call of various sociocultural societies. The role of state policy in development of multiculturalism to the Azerbaijan Republics is described.Interaction of cultures can come from violent planting of alien values and belief before full merge. But the most acceptable and correct is considered the way of dialogue of cultures. The principles of mutual understanding, mutual respect and the correct cooperation have to be the base of international dialogue. In the conclusion the conclusion is drawn on a multiculturalism role in modern society. The policyof multiculturalism is means of support of the world and stability, pledge and the guarantor of successfuldevelopment of the modern multinational state. Multiculturalism is based on the principles of respectand tolerance in relation to various ethnic groups and minorities.Key words: Multiculturalism, Azerbaijan, model, politician, nationalities.